Mealworm Ethanol Extract Enhances Myogenic Differentiation and Alleviates Dexamethasone-Induced Muscle Atrophy in C2C12 Cells - Ra-Yeong Choi; Bong Sun Kim; Eu-Jin Ban; Minchul Seo; Joon Ha Lee; In-Woo Kim (Life, 2022)
Aging, and other disease-related muscle disorders are serious health problems. Dexamethasone (DEX), a synthetic glucocorticoid, can trigger skeletal muscle atrophy. This study examined the effects of mealworm (Tenebrio molitor larva) ethanol extract (TME) on C2C12 myoblast differentiation and DEX-induced myotube atrophy. TME induced myotube formation compared to the differentiation medium (DM) group. TME also significantly increased the mRNA expression of muscle creatine kinase (CKm) and myogenic regulatory factors (MRFs), such as myogenin (MyoG), myogenic factor (Myf)5, and MRF4 (Myf6). TME dramatically increased the muscle-specific protein, MyoG, compared to the control, whereas the expression of myogenic differentiation 1 (MyoD) remained unchanged. It also activated the mammalian target of rapamycin (mTOR) signaling pathway. In the DEX-induced muscle atrophy C2C12 model, TME reduced the gene expression of atrogin-1, muscle RING finger protein-1 (MuRF-1), and myostatin, which are involved in protein degradation in skeletal muscles. Furthermore, TME elevated the phosphorylation of forkhead box O3 (FoxO3α) and protein kinase B (Akt). These findings suggest that TME can enhance myotube hypertrophy by regulating the mTOR signaling pathway, and can rescue DEX-induced muscle atrophy by alleviating atrophic muscle markers mediated by Akt activation. Thus, TME can be a potential therapeutic agent for treating muscle weakness and atrophy.